A Study of Investors Preference towards Mutual Funds in Ludhiana Stock and Capital Limited: Exploring Investor Preference towards Mutual Funds (Journal of Advances and Scholarly Researches in Allied Education, 2016)
This paper has been attempted to know preferences of investors towards mutual fund. All such Investors buy units in a fund that best suit their needs be it growth in capital, regular returns or safety of capital. For achieving the objectives primary data has been collected by the researcher through structured questionnaire.